Flexible Film-Type Sensor for Electrochemical Measurement of Dopamine Using a Molecular Imprinting Method - Kishi, Takumi; Fujie, Toshinori; Ohta, Hiroyuki; Takeoka, Shinji (Frontiers in Sensors, 2021)
Neurotransmitters, which are responsible for the signal transduction of nerve cells in the brain, are linked not only to various emotions and behaviors in our daily life, but also to brain diseases. Measuring neurotransmitters in the brain therefore makes a significant contribution to the progress of brain science. The purpose of this study is to develop a flexible thin film-type sensor that can electrochemically measure dopamine (DA) selectively and with high sensitivity. The thin-film sensor was prepared by printing gold colloidal ink on a polyimide film with a thickness of 25 µm—which the most flexible of the films examined that could maintain the buckling load (1 mN) required for insertion into the brain. The electrode (DA-PPy electrode) was then prepared by electropolymerization of polypyrrole (PPy) using DA as a template. The flexural rigidity of the sensor was 4.3 × 103 nNm, which is the lowest of any neurotransmitter sensors reported to date. When a DA solution (0–50 nM) was measured with the DA-PPy electrode using square-wave voltammetry (SWV), the slope of the calibration curve was 3.3 times higher than that of the PPy only negative control electrode, indicating an improvement in sensitivity by molecular imprinting with DA. The sensor was used to measure 0−50 nM norepinephrine (NE) and serotonin (5-HT), and the slope of the DA calibration curve at 0.24 V (19 ± 4.4 nA/nM) was much greater than those of NE (0.99 ± 3.3 nA/nM) and 5-HT (2.5 ± 2.4 nA/nM) because the selectivity for DA was also improved by molecular imprinting.